Validation of the competency profile of the nurses concerning health care - Juarez Coimbra Ormonde Júnior; Mara Regina Rosa Ribeiro; Andreia Correia de Souza Cioffi; Leonara Raddai Gunther de Campos; Adriana Freitas de Almeida Finger (Rev Rene)
Objective: to validate the content of competence for health care and its performance criteria.Methods: a cross-sectional, descriptive study using Delphi technique and a five-point Likert scale. The sample (n = 26) was composed by experts from Brazil. In order to calculate the content validity index, a degree of agreement was established in ≥80%. The analysis was performed using simple descriptive statistics. Results: the degree of agreement for the competency was 96.2% and 13 criteria were validated. Conclusion: the contents of the competence for health care and their respective performance criteria were validated by the participants. Favorable agreement demonstrates the recognition of competence as knowledge and actions in health care.